MENUMBUHKAN KREATIFITAS DALAM MENDORONG PENINGKATAN TARAF KEHIDUPAN SOSIAL EKONOMI MELALUI KEGIATAN PENGABDIAN MASYARAKAT DI DESA CEMPLANG - Zidny, Robby (Jurnal Pengabdian Dinamika, 2022)
Community service activities are the application of the Tri Dharma of Higher Education through across-scientific approach to solve problems at certain times and areas. This community service activitycarriesthetheme"GrowingCreativityinEncouragingSocio-EconomicLifeintheVillage".Community service activities are carried out for one month from January 12 to February 11, 2022 atCemplangVillage, Ciomas District, SerangRegency. The methodusedforcommunity serviceactivities is a method of counseling or socialization education directly to the community and localvillage officials. To find out the community's response to the program that has been carried out, asurvey was carried out using a Likert scale questionnaire on public perceptions. The four maincommunity service work programs have been well implemented and received positive responses fromthe community. The work programs include socializing the formation of small and medium business,socializing the application of clean and healthy living, reading gardens (Lentera Literasi), andteaching activities in schools.